Meningo - brain - acute lung disease epidemic in childhood - Cachay Diaz, H. (1959)
The relatively large number of patients of encephalitis seen by us in recent months has led us to conduct a general survey of this entity, watching intently, without prejudice, its clinical polymorphism, which can lay foundation for the right approach to your most frequent clinical forms in children.